Development of Self-Awareness and Self-Management Instruments for Children to Support Physical Bullying Intervention - Wirahandayani, Marthalisa; Octavia, Dian; Kurniawati, Kurniawati; Nadilla, Hana Syalwa (Universitas Padjadjaran, 2026)
Physical bullying in school-age children hurts emotional development and self-regulation skills. Self-awareness and self-management are two core competencies in building children's psychological resilience. However, contextually relevant measurement instruments remain limited. This study aimed to develop and validate a culturally appropriate instrument to measure self-awareness dan self-management in school-age children based on the CASEL framework. A Research and Development (R&D) approach was employed, involving indicator development grounded in relevant theory and literature, content validity assessment by two experts (a pediatric nursing expert in child pyschosocial development and an educational psychology expert in psychosocial measurement), and psychometric testing. The instrument was tested on 210 children aged 9-11 years. Construct validity was examined using Exploratory Factor Analysis, and internal consistency reliability was assessed using Cronbach's Alpha. The final isntrument comprises 58 valid and reliable items grouped into two main constructs and ten underlying factors. This instrument is suitable for further application in assessing self-awareness and self-management among school-age children who experience bullying.